The Effect Of Good Corporate Governance, Leverage, And Company Size On Tax Avoidance - Rimah Noviyani; Prisila Damayanty (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to examine the effect of institutional ownership, independent board of commissioners, audit committee, leverage, and company size on tax avoidance. The population used in this researcher is property and real estate companies on the Indonesia Stock Exchange for the 2018-2021 period. The sample in this study was 44 companies using purposive sampling. The data analysis method in this study used multiple linear regression analysis using SPSS Version 26. The results showed that institutional ownership had a significant positive effect on tax avoidance, the independent board of commissioners had a significant negative effect on tax avoidance, the audit committee had a significant negative effect on tax avoidance, leverage had a significant positive effect on tax avoidance, and the size of the company had a significant negative effect on tax avoidance.tax avoidance. Keywords: Institutional Ownership, Independent Board of Commissioners, Audit Committee, Leverage and Company Size